ANALISIS NILAI-NILAI KARAKTER DALAM LAGU “TIBA-TIBA” KARYA QUIIN SALMAN - Linda Sartika Aprilia; Sunan Baedhowi; Ari Widyaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was motivated by the emergence of modern love-themed songs which are often broadcast on television, Instagram and Tik Tok. The problem in this research is what character values ​​are contained in the song "Suddenly" by Quiin Salman? And do kids like the song "Suddenly" by Quiin Salman? Quiin Salman. The problems in this research are (1) What character values ​​are contained in the song "Suddenly" by Quiin Salman? (2) Why is the song Suddenly by Quiin Salman liked by the children of RT 05/ RW 04 Krajan, Tampingan Village, Boja District? This type of research is qualitative descriptive research. The research subjects in this qualitative research used purposive sampling. The data collection techniques used by researchers to obtain the required data from sources or other data sources are observation, interviews and documentation methods. This research focuses on analyzing the character values ​​in the song "Suddenly" by Quiin Salman. The results of this research are based on observations and interviews with children from RT 05/ RW 04 Krajan, Tampingan Village, Boja District. It can be concluded that there are 3 character values ​​that appear in the song "Suddenly" by Quiin Salman, namely: (1) Responsibility, (2) Independence and (3) Hard work. Based on this research, it is recommended that the song "Suddenly" contains role models that can be used to shape and equip children with knowledge and personality in everyday life, learning, and for life in the future. Making video clips and lyrics for the song "Suddenly" by Quiin Salman as a means of instilling character values ​​in children, as well as popularizing children's songs through various media and of course according to the age of elementary school children so that they can develop further. character in children in character in behavior in everyday life.